Adiksi Pornografi terhadap Perilaku Seksual Remaja - Anita Tiara; Rika Andriani (Journal of Telenursing (JOTING), 2023)
This study aims to determine pornography addiction to adolescent sexual behavior. This type of research uses observational analytic with a cross sectional study approach. The sample in this research is 154 people with simple random sampling method. Data were analyzed using the Chi Square test. The results showed that pornography addiction to adolescent sexual behavior obtained a p value of 0.000. The conclusion is that there is a relationship between pornography addiction and adolescent sexual behavior at SMAN 1 and SMK 1 Suka Makmue District. It is suggested to parents, teachers and religious leaders to always monitor and provide information to adolescents about pornography and premarital sexual behavior Keywords: Adolescents, Pornography, Sexual Behavior